PENGARUH MODEL THINK PAIR SHARE DAN MEDIA CROSSWORD PUZZLE UNTUK MENINGKATKAN MINAT BELAJAR MATEMATIKA SISWA SEKOLAH DASAR DI NGEMBALREJO BAE KUDUS - Taufiqur Rohman; Sri Surachmi W; Murtono (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to: (1) analyze the effect of the Think Pair Share model on students' interest in learning Mathematics at SD 2 Ngembalrejo Bae Kudus, (2) analyze the effect of crossword puzzle media on students' interest in learning mathematics at SD 4 Ngembalrejo Bae Kudus Results, (3) analyze the influence of Think Pair Share model and the crossword puzzle media on students' interest in learning mathematics at SD 5 Ngembalrejo Bae Kudus. The method used in this study was a quantitative method of data analysis with statistics. In this study, the researchers conducted a field study at one of the elementary schools in Desa Ngembalrejo. The population in this study consisted of Grade 5 students at four elementary schools, namely SD 2 Ngembalrejo, SD 4 Ngembalrejo, SD 5 Ngembalrejo, and SD 3 Ngembalrejo chosen as the control class through a simple random sampling technique. In this study, the researchers used statistical analysis, namely simple regression and correlation. The results showed that 1) the Think Pair Share model increased students' interest in learning mathematics at SD 2 Ngembalrejo Bae Kudus since it was in Good category with a score of 41 in the 41–49 interval range. 2) Crossword Puzzle media also increased students' interest in learning mathematics at SD 4 Ngembalrejo Bae Kudus in the Very Good category with a score of 41 in the 41–49 interval range. 3) Think Pair Share and Media Crossword Puzzle models increased students' interest in learning mathematics at SD 5 Ngembalrejo Bae Kudus in the Good category, with a score of 52 in the interval range of 52–62. 4) There was a significant effect of the Think Pair Share model and crosswords puzzle media on students' interest in learning mathematics at elementary school in Ngambalrejo Bae Kudus, with the regression equation of Y1 = 49.630 + 0.381X1, Y2 = 50.985 + 0.342X2, Y3 = 51.226 + 0.683X3. Thus, the Think Pair Share model had a positive and significant score of 0.336 which was included in Low category and contributed to increasing students' interest in learning mathematics by 11.27% at SD 2 Ngembalrejo. Then, the crossword puzzle media had a positive and significant score of 0.345 which was included in Low category and contributed to increasing students' interest in learning mathematics by 11.875% at SD 4 Ngembalrejo. To conclude, Think Pair Share and Media crosswords puzzle models had a positive and significant score of 0.356 which was included in the low category and contributed to increasing students' interest in learning mathematics by 12.647% at SD 5 Ngembalrejo.